Grey correlation analysis on influence factors of agricultural mechanization investment - MA Guang; CHEN Hong-jin (浙江大学学报. 农业与生命科学版)
Agricultural mechanization plays a key role in the progress of society and economy. The mechanization degree is influenced by multi-factors and simultaneously has influence on agricultural economy in many aspects. The agricultural mechanization actuality of our country was introduced and the influence of agricultural mechanization investment on mechanization degree was described. In the light of grey correlation analysis, it was found that the factors affecting agricultural mechanization investment were farmer's per capita income, agricultural labor force proportion, farming scale, gross agricultural production value, and total power for cultivation and harvest. The results indicated that, under the current condition, these methods, such as increasing farmer's income, accelerating the transfer speed of agricultural labor force to non-agricultural labor force, and implementing farming scale, would help to attract social fund, increase agricultural mechanization investment and promote the development of agricultural mechanization.